Investigating Students’ Difficulty in Understanding Idiomatic Expressions on EFL Classroom - Nurul Faradillah; Suhartini Khalik; Ibrahim Manda; Andi Sadapotto; Ahmad Abrar Averror Abrar Averror; Buhari Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
This research was conducted to measure the student's ability to understand idiomatic expressions and to find out the student’s difficulty in understanding idiomatic expressions. This research uses the descriptive qualitative method as the research methodology. The population in this study is the fourth-semester students in the English education department, faculty of teacher, training, and education of Muhammadiyah University of Sidenreng Rappang, and the sample in this study is 29 students (4 male students and 25 female) fourth semester, English department, faculties of teacher, training, and education of Muhammadiyah University of Sidenreng Rappang. The data collection methods used in this research are written test, interview, and recorder. A written test was chosen to measure students'' ability to identify idiomatic expressions, interviews were used to find out the student’s difficulty in understanding idiomatic expressions, and the recorder were used to record the interview process and also as data documentation. The data obtained from the test will be processed with a scoring technique and the data obtained from the interview will be processed by the descriptive analysis method. As the result of the study, the written test shows that 2 students categorized on a very good level, 7 on Good, 5 on Average, 3 on Poor, and 3 on very poor, while the interview shows that as many as 62% of respondents have difficulty because they lack vocabulary, 19% of respondents have difficulty understanding idioms based on their language style, and 33% of respondents have difficulty understanding idioms.